Рід Шевченкової матері Катерини Бойко - Карпінчук, Г.В. (Слово і Час, 2019)
У статті за архівними матеріалами з'ясовано родовід Шевченкової матері Катерини Бойко
від кінця XVIII ст. до середини ХІХ ст. Зокрема, установлено історію роду поета від прадіда
Омеляна Бойка; уточнено відомості про найближчих родичів Т. Шевченка – дядька Павла, тіток
Дарію, Євдокію й Ганну, розшукано інформацію про ще двох – Варвару та Мотрю. Спростовано
твердження, що по лінії матері поета спадкоємців не було. На сьогодні віднайдено відомості про
сорока вісьмох двоюрідних братів і сестер, сімдесятьох трьох племінників Т. Шевченка, трьох
внучатих небожів. Вичерпний аналіз архівних матеріалів заперечує існування Агафії Якимівни
Бойко, про яку в низці повідомлень у медіа йдеться як про матір поета. The article explores the genealogy of Shevchenko’s mother Kateryna Boyko based on archival
materials of the Central State Historical Archive of Ukraine in Kyiv, the State Archive of Kyiv Region
and the State Archive of Cherkasy Region. The author investigated this family tree starting from the
end of the 18th century and until 1859, when Shevchenko visited Ukraine for the last time. In particular,
the history of the poet’s family in connection with his grandfather Omelian Boyko was analyzed. The
assumption that family line of Shevchenko’s mother originates from Carpathian rebel and contemporary
of Oleksa Dovbush Ivan Boyko was rejected. Some details about the closest relatives of T. Shevchenko,
namely his uncle Pavlo, aunts Dariya, Yevdokiya and Anna, have been clarified. Information about
two unknown writer’s aunts Varvara and Motria has been found.
The assertion that the mother’s family line lacked descendants was refuted. The surnames in
marriage of the five Shevchenko’s aunts, having maiden surname Boyko, have been determined.
They were Varvara Kryvenko, Motria Zavaliy, Dariya Diachenko, Yevdokiya Diadenko, Hanna Shkurup.
By now we have information about forty nine poet’s cousins, seventy four nephews and three greatgrandchildren
of his aunts. The comprehensive analysis of the archival materials allows the researcher
to deny the existence of Ahafiya Yakymivna Boyko, the alleged poet’s mother according to some
media reports.
The article also refers to the administrative structure, nature and geography of the village Moryntsi
in the first half of the 19th century. The life of Ukrainian peasants is discribed based on the story
“Kniahynia” (“Princess”) by T. Shevchenko as well as archival documents and research works by
V. Hrabovetskyi, V. Orlyk, L. Pohylevych, O. Stepanyshyna.